PEMBUATAN BIBIT ANGGREK HIBRIDA DAN ADAPTASI PADA LINGKUNGANNYA MENGGUNAKAN METODE AKLIMATISASI - Dwiyani, R.; Yuswanti, H.; Astawa, I.N.G.; Mayadewi, N.N.A. (Buletin Udayana Mengabdi, 2021)
The objective of the community services was to improve the skill of housewives and other people in making of hybrid orchids.  The Training has been carried out at 24 August 2019 at The Field Station of Faculty of Agriculture, Udayana University, Denpasar.  The participants were a group of housewives and some lecturers who will get their resign in the next few years. The outcome of the current community services is an improvement of the skill of participants in making orchid hybrids through artificial pollination and also skill in aclimatisation of bottled-orchid seedlings.  This skill may increase their income because the products that have been sucseesfully made have a chance to be sold at agriculture event elsewhere or may in some nurseries that found in Denpasar.    The output of this activity is an article that will be puplished at national journal; a brief guide in making hybrid orchids ( Indosesian: Teknologi tepat guna); and products i.e. orchid seedlings in pot and capsules of orchid that resulted from artificial pollination.